Review of shielded herbicide sprayers and effects of different spray shields in spray deposition and particle drift - Gholap, Babasaheb S; Tiwari, Ghanshyam; Sharma , Ajay Kumar (Journal of Postharvest Technology, 2022)
Effective use of pesticides (Insecticide, Fungicide, Herbicides etc.) in the crop is of concern since many years. Pesticide applied through conventional  sprayers is lost through drift due to many machine factors (nozzle type, nozzle pressure, height of spraying etc.) and environmental factors (wind  direction, wind speed, temperature and relative humidity etc.). For efficient weed control sprayer must able to spray herbicides at root zone and lower  ground heights. Mechanical devices, such as protective shields which cover the sprayer boom or individual nozzles, may contribute to reduce the  amount of spray being displaced during windy conditions. This paper reviews work carried out by various researchers on development of different  shielded sprayers for insecticide & herbicide application and their role in drift reduction and efficient droplet deposition.
Keywords: Shielded sprayer; volume median diameter; drift; herbicide